The Influence Of Disruptive Environment, Value Chain Efficiency, And Logistics Agility On Logistics Innovation And Its Implications On Company Performance - Widodo, Erlangga Putragung; Waskito, Saptono Kusdanu; Lestiani, Melia Eka (Amkop Management Accounting Review (AMAR), 2025)
This study provides a comprehensive examination of the effects of three independent variables - disruptive environment, value chain efficiency, and logistics agility - on logistics innovation and its subsequent impact on company performance at PT Pos Indonesia Main Branch Office in Jember. Data collection involved a structured questionnaire distributed to 146 respondents, including managers, staff members, and distribution partners. Data analysis was conducted using Structural Equation Modeling (SEM) with SMART PLS 3 software. The results indicate that a disruptive environment - characterized by emerging technologies, market volatility, and global uncertainties - drives logistics innovation with a contribution value of 28.22%, highlighting the necessity for swift adaptation to external changes. Additionally, value chain efficiency, encompassing asset optimization and waste reduction, contributes 25.31% to innovation, while logistics agility - measured by responsiveness and digital integration - accounts for 25.75% of the innovation effect. Furthermore, logistics innovation has a significant impact on company performance, with an effect size of 70.5%. These findings underscore the critical role of cross-functional collaboration, technological investment, and human capital development in bolstering innovation capabilities. Practical recommendations include strengthening strategic partnerships, establishing internal innovation hubs, and continuously monitoring market and technology trends to sustain competitive performance in the digital era.